La pax extractiva y el conflicto socioambiental en Colombia - De Los Ríos, Sebastián (Pontificia Universidad Católica del Perú. Fondo Editorial, 2016)
The government of Colombia and the Revolutionary Armed Forces of Colombia (FARC) have signed agreements heralding an era of “peace” for the country. While the end of the confrontation brings many opportunities, it also poses numerous challenges. This article argues that the most significant of these challenges is the potential for the conflict to merely transform into a socio-environmental conflict. Indeed, the mere signing of the peace agreements does not constitute a guarantee to prevent the escalation of conflict in some regions. To prevent this, the dynamics of dialogue and consensus evidenced in the negotiations that took place in Havana must be replicated at a local level in the territories that once were dominated by the FARC. Improved security conditions deriving from the ceasefire have shown propitious for the development of extractive activities in territories previously ridden by armed conflict. But while the dynamism of the mining and energy sector provides significant opportunity for economic development, it has coincided with the intensification of socio-environmental conflict in several regions of the country. If the government does not address these rising conflicts between multi-nationals and local populations, what is now fertile ground for peacebuilding could prove to be the beginning of a new form of long-lasting violent conflict.

El gobierno de Colombia y las Fuerzas Armadas Revolucionarias de Colombia (FARC) han suscrito los acuerdos que presagian una era de “paz” para el país. Si bien el fin del enfrentamiento armado trae consigo muchas oportunidades, plantea a su vez muchos retos. La firma de los acuerdos de paz no constituye una garantía para evitar la intensificación del conflicto en algunas regiones. Las dinámicas de diálogo y concertación de las mesas de negociación de La Habana deben replicarse en los territorios que otrora fueron dominados por las FARC si no se quiere incrementar el conflicto, particularmente el socioambiental. El mejoramiento de las condiciones de seguridad que derivan del cese al fuego entre ambos bandos se ha mostrado propicio para el desarrollo de actividades extractivas en territorios donde hasta hace poco estuvieron vedadas. El reciente dinamismo del sector minero energético coincide con el escalamiento del conflicto socioambiental en numerosos territorios del país. Ante esta situación, la promoción del desarrollo por el Estado colombiano constituye un complejo desafío en el contexto de construcción de la paz.
Extractive pax and socio-environmental conflict in Colombia
Keywords: Conflicto socioambiental; Industria extractiva; Fuerzas Armadas Revolucionarias de Colombia (FARC); Ordenamiento territorial; Paz; https://purl.org/pe-repo/ocde/ford#5.09.01